SAT0728-HPR A patient satisfaction survey: patients' perceptions of biologic dose tapering. (15th June 2017) - Jones, C; Robinson, H; Rees, D; Jolliffe, V; Trickey, J; Wood, J; Andrews, S; Capillas, S; Peall, A
Abstract : Background: Evidence shows that remission can be maintained in selected patients whose biologic medication is dose tapered 1 . In June 2015 we began tapering the doses of selected rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis patients in disease remission. The process was agreed with the local commissioners and a protocol 2 was devised to guide safe and evidence based biologic dose tapering. Benefits include reduced medication burden for patients, fewer day-case infusions and financial savings. However, there is a lack of knowledge of patients' perceptions of the process. Objectives: Our department proposed to investigate patients' perceptions of their experience of dose tapering. We wanted to assess patients' understanding and acceptance of the process and ensure they felt included in decision making. Patient feedback enables reflection and improved practice. Methods: An anonymous, tick-box, patient satisfaction survey was devised. It requested that patients stated the extent to which they agreed with a statement, also allowing free-text comments. The survey was posted to relevant patients after their identification from our biologics database. A stamped addressed envelope was provided for return of the completed survey. Results: 56 surveys were posted, 46 (82%) were returned. 31 (67%) of patients were pleased to taper their medication, 35 (76%) felt fully included in decision making and 36 (78%) agreed that they had the opportunity to ask questions. Of the 13 patients whose disease flared post-taper, 8 (62%) agreed that they were promptly reviewed in clinic, 1 patient (8%) disagreed. Some admitted to anxiety prior to dose tapering, however once established on their new dose, continuing disease remission was reassuring. Patients felt that they could contact the rheumatology helpline if required. Some also expressed that their quality of life had improved due to the decreased medication burden. 6 (37.5%) of the 16 rituximab patients who replied, disagreed that they were included in the decision to dose taper. Therefore, clinicians must ensure information provided is clear, that a full discussion occurs and the patient has an opportunity to ask questions. On review, it was evident that the wording of the survey may have caused confusion for rituximab patients. The term "dose reduction" may have suggested that the dose of medication in their infusion was reduced. In practice, the patient decreased from two infusions to one. Conclusions: The majority of patients expressed that they were content with the biologic dose tapering process and felt sufficiently included in decision making. Importantly, a large proportion of patients were of the opinion that they were reviewed quickly when their disease flared. Practice can be improved from the knowledge that some patients would appreciate more communication regarding the decision to dose taper. Also, when undertaking further patient surveys, questions must be clear and unambiguous. References: JS Smolen, R Landewé, FC Breedveld, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis 2014;73:492–509. C Holloway. Wye Valley NHS Trust: Biologics in Rheumatology: Dose Tapering Protocol. Sept. 2015. Disclosure of Interest: None declared